Endocardial–epicardial distribution of myocardial perfusion reserve assessed by multidetector computed tomography in symptomatic patients without significant coronary artery disease: insights from the CORE320 multicentre study. (4th September 2015) - Kühl, Jørgen Tobias; George, Richard T.; Mehra, Vishal C.; Linde, Jesper J.; Chen, Marcus; Arai, Andrew E.; Di Carli, Marcelo; Kitagawa, Kakuya; Dewey, Marc; Lima, Joao A.C.; Kofoed, Klaus Fuglsang
Abstract: Aim: Previous animal studies have demonstrated differences in perfusion and perfusion reserve between the subendocardium and subepicardium. 320-row computed tomography (CT) with sub-millimetre spatial resolution allows for the assessment of transmural differences in myocardial perfusion reserve (MPR) in humans. We aimed to test the hypothesis that MPR in all myocardial layers is determined by age, gender, and cardiovascular risk profile in patients with ischaemic symptoms or equivalent but without obstructive coronary artery disease (CAD). Methods and results: A total of 149 patients enrolled in the CORE320 study with symptoms or signs of myocardial ischaemia and absence of significant CAD by invasive coronary angiography were scanned with static rest and stress CT perfusion. Myocardial attenuation densities were assessed at rest and during adenosine stress, segmented into 3 myocardial layers and 13 segments. MPR was higher in the subepicardium compared with the subendocardium (124% interquartile range [45, 235] vs. 68% [22, 102], P < 0.001). Moreover, MPR in the septum was lower than in the inferolateral and anterolateral segments of the myocardium (55% [19, 104] vs. 89% [37, 168] and 124% [54, 270], P < 0.001). By multivariate analysis, high body mass index was significantly associated with reduced MPR in all myocardial layers when adjusted for cardiovascular risk factors ( P = 0.02). Conclusion: In symptomatic patients without significant coronary artery stenosis, distinct differences in endocardial–epicardial distribution of perfusion reserve may be demonstrated with static CT perfusion. Low MPR in all myocardial layers was observed specifically in obese patients.